Recursos Humanos para o Sistema Único de Saúde: formação e inserção de técnicos em saúde bucal em Minas Gerais - Ana Claudia Pereira dos Santos Cruz (2018)
In order to meet the technical training demands of health service workers, the Technical Schools and Training Centers of the Unified Health System were created. The literature reveals that the number of Oral Health Technicians included in the public service is lower than that of training schools. The objective of this study was to evaluate the impact of the Oral Health Technician training conducted by the School of Public Health of the State of Minas Gerais, in the scope of graduates from 19 groups formed between 2012-2013. Two studies were carried out: the first one was transversal, ecological, and evaluated 122 municipalities participating. The objective was to investigate the possible factors associated with the insertion of the Oral Health Technician in the Unified Health System in Minas Gerais, and its implications on oral health indicators. The municipal variables selected were related to the organization of health services, oral health indicators and sociodemographic indicators, before and after the course. The dependent variable was the inclusion of egress in the public service, according to self-report for a research conducted in 2015/2016. A descriptive analysis was carried out, followed by bivariate and multivariate analyzes between the independent variables and the dependent variable, using the chi-square test by Pearson. The software SPSS® 18.0 was used. The variable "collective action indicator supervised dental brushing" showed association with the insertion, remaining in the final model. It was concluded that the implantation of the Oral Health Team modality II, positively influenced the insertion of the Oral Health Technician in the Unified Health System in Minas Gerais, with improvement in the municipal oral health indicators. The second study was transversal, descriptive, qualitative and quantitative, carried out with the teachers of the Course. The perception of the teachers in relation to the formation, insertion, actuation and contribution of the egress for the service was evaluated. A semistructured questionnaire sent by e-mail was used, which had four dimensions: sociodemographic profile, teacher training, Oral Health Technician training and egress and insertion in the Unified Health System. The response rate was 74% and 58% for the two groups evaluated. The profile found was of a majority of women, with a mean age of 40.2 years (SD ± 7.38) and 37.8 years (SD ± 8.26), who completed graduation in private educational institution and has postgraduate level of Specialization in the area of Collective Health or Public Health. The majority of participants evaluated that the training of the Oral Health Technician was in line with the proposed objectives. In relation to the low insertion of the graduates in the public service, they believe that it is due to lack of interest of the municipal management. They reported that the performance of the egress is greater in collective activities than in clinics and that the insertion contributed to the quality and productivity of oral health services. These studies show a need to reformulate the policy of permanent education in the state, aiming at optimizing the resources invested in the training of the Oral Health Technician.